Bispecific Antibodies in Cancer Immunotherapy: A Novel Response to an Old Question - Camila Ordóñez-Reyes; Juan Esteban Garcia-Robledo; Diego F. Chamorro; Andrés Mosquera; Liliana Sussmann; Alejandro Ruiz-Patiño; Oscar Arrieta; Lucia Zatarain-Barrón; Leonardo Rojas; Alessandro Russo; Diego de Miguel-Perez; Christian Rolfo; et al. (Pharmaceutics, 2022)
Immunotherapy has redefined the treatment of cancer patients and it is constantly generating new advances and approaches. Among the multiple options of immunotherapy, bispecific antibodies (bsAbs) represent a novel thoughtful approach. These drugs integrate the action of the immune system in a strategy to redirect the activation of innate and adaptive immunity toward specific antigens and specific tumor locations. Here we discussed some basic aspects of the design and function of bsAbs, their main challenges and the state-of-the-art of these molecules in the treatment of hematological and solid malignancies and future perspectives.